From Local to Global : Multidisciplinary Insights on Education, Governance, and Technology for Societal Progress: Dari Lokal ke Global: Wawasan Multidisiplin Tentang Pendidikan, Tata Kelola, dan Teknologi untuk Kemajuan Masyarakat - Marah, Thomas Sheku (DAS Institute, 2025)
Education together with governance and technology represent a core transformation that drives societal advancement throughout the twenty-first century. The intersection between these elements enables expanded knowledge access and better service delivery along with increased civic participation. Digital transformation encounters barriers because of inadequate digital infrastructure and unequal literacy rates and uncoordinated governance systems which restrict its advantages in developing countries. Solving this problem demands a combined approach which describes both the potential advantages of innovation alongside the dangers of marginalization. The research sets out to establish a combination framework which explains how governance controls technology-education interactions and their joint effects on social inclusion along with sustainable development. The research implemented mixed-methods design through bibliometric analysis of worldwide studies between 2020 and 2025 and systematic literature review and comparative case study focusing on Indonesia. The findings reveal four central themes: digital learning and resilience, e-governance and participation, technological innovation for sustainability, and ethical challenges of digitalization. The findings demonstrate that inclusive governance together with strong institutional capacity serves as the decisive factor to convert technological progress into educational and social benefits that reach everyone. The research shows that successful digital innovation transformation into sustainable societal engines needs coordinated multidisciplinary approaches.